Transcriptomic Analysis of Testicular Gene Expression in a Dog Model of Experimentally Induced Cryptorchidism - Hyunjhung Jhun; Won-Young Lee; Jin-Ki Park; Sun-Goo Hwang; Hyun-Jung Park (Cells, 2022)
Cryptorchidism, a condition in which testes fail to descend from the abdomen into the scrotum, is a risk factor for infertility and germ cell cancer. Normally, tight junctions between adjacent Sertoli cells in the testes form a blood–testes barrier that regulates spermatogenesis; however, the effect of cryptorchidism on tight junctions is not well-understood. We established a model of heat-induced testicular damage in dogs using surgical cryptorchidism. We sequenced RNA to investigate whether certain transcripts are expressed at higher rates in heat-damaged versus normally descended testes. Claudins, cell adhesion molecules, were relatively highly expressed in cryptorchid testes: claudins 2, 3, 5, 11, and 18 were significantly increased in cryptorchid testes and reduced by orchiopexy. SOX9-positive Sertoli cells were present in the seminiferous tubules in both cryptorchid and control testes. Using real-time PCR and Western blot analysis to compare Sertoli cells cultured at 34 °C and 37 °C, we found that Sertoli cell claudins 2, 3, 5, 11, and 18 were significantly increased at 37 °C; however, accumulation was higher in the G0/G1 phase in Sertoli cells cultured at 34 °C. These results indicate that testicular hyperthermia caused by cryptorchidism affects claudin expression, regulated germ cell death, and the proliferation of Sertoli cells.